DEVELOPMENT CENTER FOR ORPHANED AND NEGLECTED CHILDREN WITH A BEHAVIORAL ARCHITECTURE APPROACH IN MEDAN - Walhidayah, Tari Laricci; Marisa , Amy (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
One of the most significant social problems in large urban areas, including Medan, is the issue of neglected children. The prevalence of abandoned children is influenced by a range of factors, including economic instability, lack of preparation for parenthood, and family disharmony. It is not uncommon to find these children in locations such as crossroads and public spaces, where they may be offering services or requesting donations. In light of the rising population of Medan City, it is imperative to devise a unique solution for the care of abandoned children. Therefore, it is important to design a development center for orphaned and neglected children which a adopts a behavioural architecture approach. This approach is designed to create spaces that support children’s psychological and physical well-being, facilitate their activities, and provide moral teaching and education to prepare them for social life. This research employs a descriptive qualitative methodology, utilising a combination of primary and secondary data collection, a literature review and a field survey. The results show that the design of center for orphaned and neglected children should be able to meet the needs of children for self-develop and their daily activities.